Determination of Share Prices in Automotive Manufacturing Companies - Amril, Elviani; Sukraini, Juita; Defitri, Siska Yulia (Institut Bisnis dan Informatika Kesatuan, 2024)
Economic development and growth have increased significantly in the era of globalization. The capital market is one source of economic development in a country which has an important role as a means of financial funding for a company so that it can obtain financial resources from investors. The capital market provides long-term financial instruments with a maturity of more than one year, such as shares, bonds or what are usually called debentures, mutual funds and Exchange Traded Funds/ETFs, as well as derivatives. This aims of the research was to determine and analyze the influence of fundamental company conditions, the rupiah exchange rate and (Sertifikat Bank Indonesia/SBI) interest rates on share prices. This research used quantitative research and an associative approach carried out on automotive manufacturing companies listed on the IDX in 2018-2022. The total sampling technique was chosen for sampling. The results of this research are that the fundamental conditions of the company have a significant effect on share prices, while the rupiah exchange rate and SBI interest rates do not have a significant effect on share prices. This means that investors can consider the fundamental conditional condition of the company when they want to invest in shares, this research because a decrease or increase in the DER can affect the share price of automotive companies listed on the Indonesian Stock Exchange in 2018-2022.